Metagenomic analysis reveals gut bacterial signatures for diagnosis and treatment outcome prediction in bipolar depression. (January 2022) - Lai, Jianbo; Li, Ang; Jiang, Jiajun; Yuan, Xiuxia; Zhang, Peifen; Xi, Caixi; Wu, Lingling; Wang, Zheng; Chen, Jingkai; Lu, Jing; Lu, Shaojia; Mou, Tingting; et al.
Highlights: Metagenomic analysis showed altered gut microbiota in patients with bipolar depression. Quetiapine monotherapy impacted the diversity and composition of the gut microbiota. Clostridium bartlettii abundance was positively related to spontaneous neural oscillation in the hippocampus. Gut microbe-based models showed favorable efficacy for diagnosis and treatment outcome prediction. Abstract: Background: We aimed to characterize gut microbial alterations in depressed patients with bipolar disorder (BD) following quetiapine monotherapy and explored its potential for disease diagnosis and outcome prediction. Methods: Fecal samples were obtained from 60 healthy individuals and 62 patients in acute depressive episodes. All patients received one-month quetiapine treatment after enrollment. The structure of gut microbiota was measured with metagenomic sequencing, and its correlation with clinical profiles and brain function as indicated by resting-state functional magnetic resonance imaging was analyzed. Random forest models based on bacterial species were constructed to distinguish patients from controls, and responders from non-responders, respectively. Results: BD patients displayed specific alterations in gut microbial diversity and composition. Quetiapine treatment increased the diversity of microbial communities and changed the composition. The abundance of Clostridium bartlettii was negatively associated with age, baseline depression severity, while positively associated with spontaneous neural oscillation in the hippocampus. Tree-based classification models for (1) patients and controls and (2) responders and non-responders showed an area under the curve of 0.733 and 0.800, respectively. Conclusion: Our findings add new evidence to the existing literature regarding gut dysbiosis in BD and reveal the potential of microbe-based biomarkers for disease diagnosis and treatment outcome prediction.